The role of antigen presenting cells in the induction of HIV-1 latency in resting CD4(+) T-cells - Kumar, Nitasha A. (Retrovirology, 2015)
BACKGROUND: Combination antiretroviral therapy (cART) is able to control HIV-1 viral replication, however long-lived latent infection in resting memory CD4(+) T-cells persist. The mechanisms for establishment and maintenance of latent infection in resting memory CD4(+) T-cells remain unclear. Previously we have shown that HIV-1 infection of resting CD4(+) T-cells co-cultured with CD11c(+) myeloid dendritic cells (mDC) produced a population of non-proliferating T-cells with latent infection. Here we asked whether different antigen presenting cells (APC), including subpopulations of DC and monocytes, were able to induce post-integration latent infection in resting CD4(+) T-cells, and examined potential cell interactions that may be involved using RNA-seq. RESULTS: mDC (CD1c(+)), SLAN(+) DC and CD14(+) monocytes were most efficient in stimulating proliferation of CD4(+) T-cells during syngeneic culture and in generating post-integration latent infection in non-proliferating CD4(+) T-cells following HIV-1 infection of APC-T cell co-cultures. In comparison, plasmacytoid DC (pDC) and B-cells did not induce latent infection in APC-T-cell co-cultures. We compared the RNA expression profiles of APC subpopulations that could and could not induce latency in non-proliferating CD4(+) T-cells. Gene expression analysis, comparing the CD1c(+) mDC, SLAN(+) DC and CD14(+) monocyte subpopulations to pDC identified 53 upregulated genes that encode proteins expressed on the plasma membrane that could signal to CD4(+) T-cells via cell–cell interactions (32 genes), immune checkpoints (IC) (5 genes), T-cell activation (9 genes), regulation of apoptosis (5 genes), antigen presentation (1 gene) and through unknown ligands (1 gene). CONCLUSIONS: APC subpopulations from the myeloid lineage, specifically mDC subpopulations and CD14(+) monocytes, were able to efficiently induce post-integration HIV-1 latency in non-proliferating CD4(+) T-cells in vitro. Inhibition of key pathways involved in mDC-T-cell interactions and HIV-1 latency may provide novel targets to eliminate HIV-1 latency. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12977-015-0204-2) contains supplementary material, which is available to authorized users.